PENGARUH TATA KELOLA PERUSAHAAN TERHADAP PENGUNGKAPAN MANAJEMEN RISIKO - Michael Lokaputra; Pipin Kurnia; Rita Anugerah (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2022)
Disclosure of risk management is a disclosure of the risks that have been managed by the company or disclosure of how the company will control risks related to the future. The purpose of this study was to determine the effect of corporate governance such as managerial ownership, institutional ownership, independent commissioners, audit committees and risk management committees on risk management disclosure. The population of this study are non-bank financial services companies listed on the Indonesian stock exchange in 2016-2019. The sample selection method was carried out by purposive sampling, namely the method of selecting samples with certain criteria. The sample according to the criteria is 31 companies with an observation period of 4 years so that the research sample is 124. Based on multiple regression analysis, the results of this study indicate that managerial ownership has an effect on risk management. Furthermore, institutional ownership factors affect risk management management. The independent commissioner factor has no significant effect on risk management. the audit committee has an effect on the assessment of risk management factors. Risk management factors affect risk management management.